Ocins for Food Safety - Choyam, Shilja; Srivastava, Alok Kumar; Shin, Jae-Ho; Kammara, Rajagopal (Frontiers in Microbiology, 2019)
Ocins (bacteriocins/lactocins/enterocins) are antibacterial proteins synthesized by gut bacteria that kill or suppress the growth of related or unrelated bacterial strains. Food industry producing perishable and vulnerable products such as vegetables, milk products, and meat are susceptible to deterioration by spoilage and pathogenic bacteria, and microbial decomposition presents a severe problem for food manufacturers. It is essential to find broader, better, and more effective preservation solutions to prevent food spoilage. The traditional methods of sterilization either by mechanical means or by use of antibiotics may not be sufficient as many major microbes are resistant. Ocins offer a promising strategy for food preservation because of their antagonism towards pathogenic microbes. Many ocins have been characterized and studied biochemically and genetically; however, their structure-function relationships, biosynthesis, and modes of action are not well understood. This review focuses primarily on various ocins and their relevance to the food industry to help produce germ-free foods. In particular, the utilization of various ocins directly by the food industry is highlighted.